Efektivitas Kasasi Demi Kepentingan Hukum Dalam Sistem Peradilan Pidana - Muhammad Ridha (Lex Renaissance, 2021)
This study aims to analyze the effectiveness of extraordinary cassation legal remedies for the sake of the law and examine the revitalization of extraordinary cassation legal remedies for legal purposes in the future criminal justice system. This research is a normative juridical law research that uses a statutory approach to analyze the legal issues raised. The results of this study indicate that first, the ineffectiveness of legal remedies in the form of cassation for the sake of the law is caused by the substance of the article that regulates the legal remedies that are essentially aimed at protecting and safeguarding the rights of the convict. Second, the effort to revitalize the Criminal Procedure Code is aimed at making extraordinary legal efforts in the form of cassation for the sake of the law run effectively, namely by returning the right to legal remedies for cassation for the sake of the law to the public prosecutor, and revising the article that became the root of the problem of ineffectiveness.Key Words: Cassation for the Interest of the law; criminal justice system; effectivityAbstrakPenelitian ini bertujuan untuk menganalisis efektifitas upaya hukum luar biasa kasasi demi kepentingan hukum dan mengkaji revitalisasi upaya hukum luar biasa kasasi demi kepentingan hukum dalam sistem peradilan pidana yang akan datang. Penelitian ini merupakan penelitian hukum yuridis normatif yang menggunakan pendekatan perundang-undangan untuk menganalisis permasalahan hukum yang diangkat. Hasil penelitin ini menyimpulkan bahwa pertama, ketidakefektifan upaya hukum berupa kasasi demi kepentingan hukum disebabkan oleh substansi pasal yang mengatur upaya hukum tersebut pada hakekatnya bertujuan melindungi dan menjaga hak terpidana. Kedua, upaya merevitalisasi kembali Kitab Hukum Acara Pidana bertujuan agar upaya hukum luar biasa berupa kasasi demi kepentingan hukum dapat berjalan efektif, yaitu dengan cara mengembalikan hak upaya hukum kasasi demi kepentingan hukum tersebut kepada jaksa penuntut umum, dan merevisi pasal yang menjadi akar permasalahan ketidakefektifan tersebut.Kata Kunci: Efektivitas; kasasi demi kepentingan hukum; sistem peradilan pidana